Pengaruh Pergaulan Sesama Siswa terhadap Akhlak Siswa di SMP Negeri 1 Panyabungan Mandailing Natal - Mahdawani Tanjung; Syamsiah Depalina Siregar (Jurnal Pendidikan dan Humaniora Rumbio, 2026)
This study aims to determine the influence of peer interaction on students' moral behavior at SMP Negeri 1 Panyabungan Mandailing Natal. The research method used is quantitative with a descriptive correlational approach. Data were collected through questionnaires, observations, and interviews with 60 eighth-grade students. The results show that peer interaction has a significant influence on students’ moral formation, including discipline, responsibility, and respectfulness. Positive friendships contribute to better morals, while negative peer interactions tend to decrease moral quality. Therefore, peer relationships are essential factors in shaping students’ moral and character development at school.